Modelling Employers’ Adoption of Assistive Technology in Advancing Employment for Persons with Disabilities - RUSDI, SYEZREENDALINA; OTHMAN, NOR AZAIRIAH FATIMAH; OMAR, MUHAMAD KHALIL (The journal of contemporary issues in business and government, 2021)
Employers nowadays should stop worrying about accommodating disabled employees as appropriate assistive technologies (AT) could be adopted that fit with their employees’ limitations and help them work independently. Yet, little consideration is given to examining the adoption of AT by employers for employees with disabilities. As a result, the purpose of this study is to determine how an employer decides to adopt technology for their disabled employees and to look for any significant differences between gender and willingness to hire a disabled worker.This study's survey was conducted among 33 Small and Medium Enterprises (SMEs) in Klang Valley, Malaysia. The judgement sampling technique is utilizsed for this study, where the selection of samples will be among the managers, officers or executives in charge of managing the disabled workers. This study has specifically examined the office assistant apps as the particular AT for disabled people that the government supplied to disabled communities (hearing aids, artificial legs, etc.). The result showed a positive and significant relationship between AT Perceived Usefulness and Intention to Adopt AT. In conclusion, this study provides comprehension of the extent of employers' readiness and interest in providing AT for their disabled employees to improve their capabilities.